Measuring the success of urban renewal through residents’ lived experiences: A participatory assessment of community well-being, economic opportunity, and historical identity - Rahmayati, Yenny; Alkharashi , Norah (The Journal of City: Branding and Authenticity, 2025)
Background: Medina Al-Munawara, Saudi Arabia is one of the oldest holy cities for Muslims prominent for its historical significance as the site of the twelfth Islamic battle. The city had faced challenges of poor building quality and urban planning, prompting Governor Prince Faisal bin Salman to initiate a transformative project to enhance living conditions. Focusing on Hamra’a Al-Assad neighborhood, this research examines the urban improvement project under that initiative. Unlike most common urban improvement research that mostly focuses on design aspects, this study uniquely prioritizes residents' perceptions to comprehensively assess the success of the project. Methods: A quantitative research approach, employing a semi-structured online questionnaire with both closed and open-ended questions, delves into aspects such as daily life impact, community empowerment, economic opportunities, historical awareness, and overall satisfaction. Targeting Hamra’a Al-Assad residents, the primary users of the neighborhood, the study surpassed expectations with 102 collected responses, facilitated by collaboration with local authorities for widespread outreach. The collected data undergoes careful analysis using patterns and connections, empowering residents and providing valuable insights for decision-making in current and future urban redevelopment projects in Medina Al-Munawara. Findings: The study showed that 38.5% of residents felt safer and 50% noted increased property values, but only 28.4% saw better economic opportunities, 35.5% felt stronger community ties, 45% perceived a positive cultural impact, and just 28.4% participated in planning, revealing key gaps in engagement and inclusivity. Conclusion: This research emphasizes residents' perspectives and informs practical decisions that prioritize community well-being and inclusiveness in urban redevelopment. Novelty/Originality of this article: The novelty of this research lies in its emphasis on a resident-centric framework for evaluating urban redevelopment in a culturally and historically significant city, addressing a critical gap in the existing literature that often overlooks the socio-cultural dimensions of urban renewal in Islamic contexts.